Políticas públicas en democracia : institucionalidad y experiencia chilena 1990-2006, por, Edgardo Boeninger, Santiago : Uqbar Editores, 2007 - Gamboa Valenzuela, Ricardo (Estudios Internacionales, 2008)
-